Msia Kibona Clark. Hip-Hop in Africa: Prophets of the City and Dustyfoot Philosophers - Rantala, Janne (International Library of African Music, 2019)
pages: 171-175
Keywords: Book reviews; Hip-hop; Urban Culture; Dustyfoot Philosophers; African Music